Jurnal Web Design : Display Jasa UMKM Siko Laundry Lewat Website Strategi Promosi melalui Website guna Meningkatkan Pendapatan pada UMKM Siko Laundry - Bima Rinaldi; Hafid Barlian (CV. ITTC INDONESIA, 2024)
This base learning project explains about increasing revenue in Siko Laundry MSME services by displaying the services offered by Siko laundry on the Website. MSMEs usually tend to promote in an offline way so that the business or MSME is slow to develop, in terms of income is also limited to certain areas. Before creating an MSME Website, an analysis is first carried out about the behavior of consumers who usually wash at Siko Laundry, so that we can analyze what features and themes are appropriate for the Website we will create. Additionally, the journal emphasizes the importance of creating valuable and engaging content that matches the interests, needs, and desires of visitors/consumers. Additionally, the journal emphasizes the importance of creating valuable and engaging content that matches the interests, needs, and desires of visitors/consumers. In addition, the proposed strategy also includes search engine optimization techniques to ensure better visibility and discovery of the Siko laundry website. By optimizing keywords, meta tags, and other page elements, Disokuin can improve its search rankings. In conclusion, this study provides education for the development of Siko Laundry's digital marketing using the Website.Through a targeted approach to consumer behavior analysis, content creation, search techniques, and social media integration, Siko Laundry can build a strong online market and be able to compete with other laundry services both in Padang City and in West Sumatra.